Engagement Class with Wiggle Bot Project Based Learning - Permana, Handjoko; Bakri, Fauzi; Muliyati, Dewi; M, M. Rizki Diva; Rachmawati, Siti; R, Gustama Wibawa; Mutoharoh, Mutoharoh (MJI Publisher by PT Mitra Jurnal Indonesia, 2024)
This training emphasizes the implementation of the Project Based Learning model and Wiggle Bot as learning tools to enhance teacher engagement as training participants with knowledge about the STEM approach in modern education. In this training session, the teachers worked in groups to design and create a Wiggle Bot, which will then be integrated into the curriculum. After successfully making the Wiggle Bot, the teachers identified the STEM components present in it. This aims to enable teachers to create various STEM projects that align with the learning and concepts of the material taught in class, thereby capturing the students' attention and indirectly engaging them actively in classroom learning. The active involvement of teachers as participants indicates positive feedback from this training. This training not only enhances teachers' skills but also deepens their understanding of STEM concepts and approaches.